Nanotecnología: herramienta inteligente para la conservación del patrimonio arquitectónico y urbano (2016)
The article examines the smart and noninvasive methodologies that nanotechnology are developing for the maintenance, preservation and restoration of heritage buildings. Are included: a summary of the origin and evolution of nanotechnology; the most important advances in intelligent maintenance of the architectural and urban heritage; and the results achieved in implementing the new generation of nanostructured composite over more common construction materials in heritage works. We conclude that treatment of heritage buildings with nanocomposites allows more efficient maintenance of them, contributing to their conservation, and is creating new and highly effective processes for restoration of tangible cultural heritage of humanity.